“I am Speaking French but I am thinking in English”: An Analysis of Errors by Students of the French Language at the University of Ghana - Chachu, S. (Ghana Journal of Linguistics, 2016)
This paper is in the domain of language acquisition and more particularly foreign language learning using the theoretical framework of Error Analysis but also taking into account the concept of the development of Interlanguage during the learning of a foreign language. We consider how learners of French as a Foreign Language in the University of Ghana seem to fall, either consciously or unconsciously, on the English Language during their oral and written productions. For this study, first and second year students of French from the University of Ghana were given a series of images and asked either to describe what they saw and/or to use the images to tell a story or form a dialogue. It was observed that there was evidence of English structures, transpositions, transliterations, etc. in their productions. We consider that these interferences are part of the development of the Interlanguage of the learners and we examine some of the types of errors identified in the production of the students. We conclude that this is a natural process for the learner of a foreign language in a multilingual context and we consider how the teacher of a foreign language class can take advantage of these productions to improve his teaching and also improve learning by his/her students.
Research Article
Keywords: Error analysis; transference; Foreign Language Learning; Interlanguage; English; French